Manual de técnicas para el diagnóstico de las enfermedades ovinas. - Mogollón Galvis, J.D.; Grieve, A.; Hernández de Galvis, A.L.; Perry, B.D. (Instituto Colombiano Agropecuario, 2018)
Ovinos-Ganado ovino - Ovis aries